The effects of thermalization on the performance of passively Q-switched IC-OPOs - Kneller, Josh; Salimian Rizi, Saeed; Flannigan, Liam; Xu, Chang-qing (Frontiers in Physics, 2024)
In this paper, we report a new model for passively Q-switched intracavity optical parametric oscillators (IC-OPOs), using Cr:YAG as a Q-switch crystal. The model considers the effects of thermalization in the Nd:YAG laser crystal, excited state absorption in the Cr:YAG saturable absorber, nonlinear loss due to pump depletion in the nonlinear crystal, the thermal lens effect and the mode overlap of the fields within the nonlinear crystal. The model is able to accurately model the pulse widths and profiles of the IC-OPO, which has not been reported. The calculated pulse width for the 1064 nm pump light was 6.2 ns compared to the experimental result of 6 ns, while the signal wave was calculated to have a pulse width of 1.75 ns compared to the experimental result of 2 ns.